Synthesis of (Li1−xFex)OHFeSe and FeSe single crystals without using selenourea via a hydrothermal method. (February 2020) - Yi, Xiaolei; Qin, Lingyao; Xing, Xiangzhuo; Lin, Bencheng; Li, Meng; Meng, Yan; Xu, Mingxiang; Shi, Zhixiang
Abstract: By hydrothermal method, large and high-quality (Li1− x Fe x )OHFeSe and FeSe single crystals have been successfully synthesized without using selenourea that is an expensive commercial reagent usually used as one of the raw materials in hydrothermal condition. It is found that (Li1− x Fe x )OHFeSe single crystals synthesized in the absence of selenourea exhibit superconducting transition temperature T c as high as 40 K and critical current density J c up to 8 × 10 5 A/cm 2 ( T  = 3 K, self-field), which are comparable to or even slightly larger than those of the ones synthesized with selenourea. Meanwhile, study of the pining mechanism suggests that the main pinning sources in (Li1− x Fe x )OHFeSe single crystals are surface-like defects. Also, in order to further verify whether selenourea is of great importance in hydrothermal condition, sizable FeSe single crystals with T c of 7.2 K are also successfully synthesized without using selenourea. Accordingly, our experimental findings demonstrate that the selenourea is not indispensable during the hydrothermal process and provide a highly cost-effective way of (Li1− x Fe x )OHFeSe and FeSe single crystals preparation via a hydrothermal method. Highlights: (Li1− x Fe x )OHFeSe and FeSe single crystals were successfully synthesized without using selenourea by hydrothermal method. The main pinning sources in (Li1− x Fe x )OHFeSe are surface-like defects. Our results indicate that additional selenourea in hydrothermal conditions have little impact on the single crystal growth.